CBSE Class 8CBSE
Share
Notifications

View all notifications

Multiplying a Monomial by a Monomial - Multiplying Three Or More Monomials

Login
Create free account


      Forgot password?

notes

Observe the following examples. 
(i) `4xy × 5x^2y^2 × 6x^3y^3` = `(4xy × 5x^2y^2) × 6x^3y^3`

`= 20x^3y^3 × 6x^3y^3 = 120x^3y^3 × x^3y^3` 

`= 120 (x^3 × x^3) × (y^3 × y^3) = 120x^6 × y^6` 

`= 120x^6y^6`
It is clear that we first multiply the first two monomials and then multiply the resulting monomial by the third monomial. This method can be extended to the product of any number of monomials.

S
View in app×